2014
DOI: 10.3109/09553002.2014.955144
|View full text |Cite
|
Sign up to set email alerts
|

Cellular dosimetry calculations for Strontium-90 using Monte Carlo code PENELOPE

Abstract: The MC code PENELOPE may prove useful for cellular dosimetry involving radiation transport through materials other than water, or for complex distributions of radionuclides and geometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…On the other hand, Šefl et al (2015) utilized radionuclides ( 125 I, 111 In and 99m Tc) as the sources of radiation, and the maximum difference with MIRD was around 6%. Hocine et al (2014) calculated the cellular S-values of 90 Sr, using Penelope MC code and validated their results using the corresponding MIRD data. They reported a relative difference of less than 2.5% for the self-absorption and less than 4% for the cross-absorption S-values.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, Šefl et al (2015) utilized radionuclides ( 125 I, 111 In and 99m Tc) as the sources of radiation, and the maximum difference with MIRD was around 6%. Hocine et al (2014) calculated the cellular S-values of 90 Sr, using Penelope MC code and validated their results using the corresponding MIRD data. They reported a relative difference of less than 2.5% for the self-absorption and less than 4% for the cross-absorption S-values.…”
Section: Discussionmentioning
confidence: 96%
“…In the majority of investigations the results were compared with the MIRD S-values and/or similar data derived from other MC codes. While some papers report only minor differences between their results and corresponding MIRD data (Tung et al 2004, Hocine et al 2014, in others considerable differences were found (Bousis et al 2009, Liu et al 2009, Cai et al 2010, Freudenberg and Kotzerke 2010, Tajik-Mansoury et al 2016. To some extent, the inconsistency may be due to the physics models implemented and the cross-section tables used in simulations.…”
Section: Introductionmentioning
confidence: 93%
“…, Hocine et al 2014, Kreuzer et al 2014, Van der Meeren et al 2014, Vostrotin et al 2014, Zhivin et al 2014, Zhou 2014);(2) Biodosimetry, molecular biology and biochemistry, Mostapha et al 2014); (3) Biokinetics, Giussani 2014, Leggett et al 2014); (4) Medical countermeasures and decorporation, Bardot 2014, Griffiths et al 2014a, Griffiths et al 2014b, Kastl et al 2014, Leiterer et al 2014). …”
mentioning
confidence: 99%